The Effect Of Audit Committee And Capital Structure On Financial Performance In Energy Sector Companies Listed On The Indonesia Stock Exchange - Mutiara Raudatul Jannah; Amellia Pratiwi; Farah Margaretha Leon (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The purpose of this study is to obtain empirical evidence regarding the influence of independent variables consisting of audit committee size, audit committee independence, audit committee financial expertise and capital structure on financial performance. The companies used in this study are energy sector companies listed on the Indonesia Stock Exchange (IDX) from 2018-2023. The number of research samples was 17 companies with a total of 102 data that met the criteria using the purposive sampling method. The results of the study obtained are that the size of the audit committee and capital structure have a positive significant effect on financial performance. Meanwhile, the variables of the independence of the audit committee and the financial expertise of the audit committee have no effect on financial performance. This study builds on previous research by adding capital structure variables as independent variables. The implication of this research that has been carried out is to provide direction for financial managers in terms of selecting competent audit committee members and paying attention to the management of the capital structure in order to achieve the company's goals. For investors, it is best to choose a company that has an effective audit committee and a balanced capital structure.